2017
DOI: 10.1039/c6fo01708h
|View full text |Cite
|
Sign up to set email alerts
|

Negative effects of divalent mineral cations on the bioaccessibility of carotenoids from plant food matrices and related physical properties of gastro-intestinal fluids

Abstract: Carotenoid intake and tissue levels have been frequently associated with reduced risk of chronic diseases. However, their bioavailability is low and influenced by many dietary related parameters. Divalent mineral cations have been suggested to interfere with carotenoid digestion and to hamper micellarization, a prerequisite for their uptake, via complexation of bile salts and precipitation of fatty acids. In the present investigation, we have evaluated the effects of increasing concentrations of magnesium (0-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 50 publications
(59 reference statements)
4
29
0
Order By: Relevance
“…Similar as for earlier in vitro studies with calcium Corte-Real, Bertucci et al, 2017;Corte-Real et al, 2016), it was found that increasing the concentration of magnesium significantly decreased the bioaccessibility of all individual and total carotenoids, especially at the highest concentration of 400 mg/ L, chosen to reflect a supplement containing approximately the RDA (400 mg/d for adult men). The observed effects were in line with a decreased absolute zeta potential of the micellar fraction, suggestive of rather less stable particles.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Similar as for earlier in vitro studies with calcium Corte-Real, Bertucci et al, 2017;Corte-Real et al, 2016), it was found that increasing the concentration of magnesium significantly decreased the bioaccessibility of all individual and total carotenoids, especially at the highest concentration of 400 mg/ L, chosen to reflect a supplement containing approximately the RDA (400 mg/d for adult men). The observed effects were in line with a decreased absolute zeta potential of the micellar fraction, suggestive of rather less stable particles.…”
Section: Discussionsupporting
confidence: 75%
“…Previously, we reported that varying concentrations of divalent minerals, including magnesium, can significantly affect the in vitro bioaccessibility of carotenoids, either of pure standards or from food sources Corte-Real, Bertucci et al, 2017;Corte-Real et al, 2016), with the limitation that static in vitro models were used, with only 1 fixed concentration for bile extract and pancreatin, and thus digestive enzymes. For this reason, we here Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations